Science Subject Specific Pedagogy to Support Disaster Risk Reduction in Education: Its Feasibility and Influence - Rizki Arumning Tyas; Pujianto Pujianto; Suyanta Suyanta; Dalinem Dalinem (Berkala Ilmiah Pendidikan Fisika, 2023)
As a country with a high level of vulnerability to volcanic disasters, Indonesia must have good preparedness in dealing with these disasters. One of the efforts to improve preparedness is through learning in schools so that the community has been introduced to disaster mitigation from an early age. This study aims to (1) produce a science subject-specific pedagogy that is integrated with volcanic eruption disasters and (2) find out the effectiveness of the use of integrated science subject-specific pedagogy of volcanic eruption disasters to students’ disaster concept mastery and preparedness in disaster mitigation. This research is R&D research with a 4-D model consisting of define, design, develop, and disseminate. The subject of this study was 7th-grade students whose school is located in a disaster-prone area for the eruption of Mount Merapi, Yogyakarta. Data were obtained from tests and non-tests, including concept mastery tests, preparedness tests, questionnaires, and performance observations. The data were analyzed descriptively using MANOVA's gain score and inferential statistics using the SPSS 22.0 program. The results of this study show that (1) the science subject-specific pedagogy product developed is included in the very good category based on validation results from expert and learning practitioners, and (2) science subject-specific pedagogy is effective for improving students’ disaster concept mastery and student preparedness in facing disasters. Overall, this science subject-specific pedagogy product is feasible for science learning and has been proven to improve students' preparedness and mastery of concepts regarding volcanic eruption disasters.